Cover Jurnal Fitopatologi Vol. 19 No. 3, Mei 2023 - Editors Jurnal Fitopatologi Indonesia (Jurnal Fitopatologi Indonesia, 2023)
This editorial contains the front cover, editorial page, and back cover of the Jurnal Fitopatologi Indonesia Vol. 19 No. 3, May 2023